Biochemical studies on the effect of Crataegus aqueous extract on oxidative stress during ischemia/reperfusion induced myocardial injuries - Mohammed, Mustafa T. (Journal of the Faculty of Medicine Baghdad, 2015)
Background: myocardial ischemia-reperfusion (I/R) injury may occur in a variety of clinical settings and this remains a significant problem. Oxygen free radicals, produced on reperfusion have been shown to play a major role in myocardial I/R injury. Various therapeutic effects have been described for Crataegus. Additionally, it has been presented that Crataegus has protective effect against ischemia reperfusion induced myocardial injuries to various organs. Therefore, it seems possible that the administration of Crataegus might protect the heart against the ischemia reperfusion injury.Objectives: I detected the chemical components and trace elements of the aqueous extract of Crataegus leaves and determine whether Crataegus extract prevents or decreases ischemia-reperfusion induced myocardial injuries in rats.Methods: The chemical composition of the aqueous extracts of the Crataegus leaves was analysed and concentration of some trace elements was estimated .Thirty-six rats were divided into three groups as control, I/R group and Crataegus treatment group. Blood samples were taken from the rats for the biochemical parameters estimating, serum aspartate aminotransferase (AST), alanine aminotransferase (ALT), lactate dehydrogenase (LDH) oxidative stress levels of nitric oxide (NO) and lipid peroxidation (LPO).Results: The results showed that the extract contain: glycosides saponins, tannins ,phenolic compounds , proteins and flavonoids . The results also showed that there were high concentrations of K , Na , Ca with (171.2 , 19 , 18.3) ppm, respectively and low concentrations of Fe, Zn ,Cu, Mg with (5.1, 3.2 ,2.3 ,1.9) ppm, respectively ,very low concentrations Cr ,Cd , Pb with (0.9 ,0.7, Nil) ppm . The levels of heart enzymes and Oxidative stress in group 3 were significantly lower than those in the group 2.Our results suggest that Crataegus treatment protects the rat heart against ischemia-reperfusion induced myocardial injuries.Conclusion: The present study confirms that the aqueous extract of Crataegus contains (glycosides, tannins, proteins, saponins, phenolic compounds and flavonoids) as well as our results suggest that Crataegus treatment protects the rat heart against ischemia-reperfusion induced myocardial injuries .